(untitled) (International journal of artificial intelligence, 2026)
The integration of innovative technologies in medical education is revolutionizing traditional pedagogical approaches, fostering not only clinical competence but also the development of healthy thinking—characterized by resilience, empathy, critical reasoning, and emotional well-being. This article explores immersive simulations, artificial intelligence-driven tutoring, digital mental health interventions, and collaborative platforms as transformative tools. By prioritizing student-centered ecosystems, these technologies address the high-stress environment of medical training, enhancing knowledge retention, skill acquisition, and psychological health while preparing future physicians for holistic patient care.